Exploring the Potentials and Pitfalls of Artificial Intelligence-Driven Decision-Making (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
As artificial intelligence (AI) becomes more deeply implied in everyday life, it takes a more prominent role in decision-making in every industry. As Joseph Fuller, a professor of management practice at Harvard Business School, said: “Virtually every big company now has multiple AI systems and counts the deployment of AI as integral to their strategy.” Implicitly, decision-making capabilities are incorporated into their products; consequently, ethical concerns also gain importance. This paper presents some of the most critical issues of using AI in everyday decision-making. Starting from the three main concepts of AI, decision-making and ethics, it is a philosophical approach to the issues and biases raised by AI's overwhelming spread in everyday life.